Potential Mechanisms of Quercetin Influence the ClfB Protein During Biofilm Formation of Staphylococcus aureus - Kang, Xinyun; Ma, Qiang; Wang, Guilai; Li, Na; Mao, Yanni; Wang, Xin; Wang, Yuxia; Wang, Guiqin (Frontiers in Pharmacology, 2022)
This study aimed to establish the mode of binding between quercetin and an essential protein called ClfB in forming biofilm in Staphylococcus aureus. In this study, the raw data of GSE163153 were analyzed for quality control, alignment, and gene counts, and the differential analysis detected the key differentially expressed genes (DEGs) assisting in the formation of the Staphylococcus aureus biofilm. Then, the protein-protein interaction (PPI) and gene function enrichment analyses of the target genes, identified a gene called clfB to be closely related to biofilm formation. ClfB was structurally characterized, molecularly docked, and kinetically simulated to unravel the mode of binding of quercetin to ClfB. Meanwhile, the growth curve and transmission electron microscopy methods examined the effect of quercetin on the Staphylococcus aureus growth. Results indicated that the clfB gene was increasingly expressed during biofilm formation and was involved in cell adhesion, pathogenicity, and infection. We identified 5 amino acid sites of ClfB (D272, R331, I379, K391, E490) as potential sites for binding quercetin, which would have an indirect influence on the changes in the functional sites N234, D270, Y273, F328 inhibiting the formation of biofilm. Meanwhile, 128 μg/ml of quercetin could significantly inhibit the Staphylococcus aureus biofilm formation. This manuscript serves as a molecular foundation for quercetin as an antibacterial drug providing a new perspective for developing antibacterial drugs.